Reflexos da lei de liberdade econômica na regulaç\~ao ambiental brasileira - Nilo Luiz Saccaro Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Federal Law No. 13.874/2019, known as the Economic Freedom Act, has strong effects on regulatory policies, including environmental regulation. This work aims to identify the provisions of the Economic Freedom Act that may affect the creation and application of environmental standards, as well as the regulations and mechanisms that moderate such impact, assessing their compatibility with the principles of environmental law and the constitutionally guaranteed right to an ecologically balanced environment. Through a normative analysis of each chapter of the Economic Freedom Act and other related normative instruments, it is concluded that the Act is capable of reconciling principles of economic freedom and environmental law, contributing to a better balance in the pursuit of sustainable socioeconomic development.
Keywords: K32; 330; agricultural structure; export crops; midwest